Impact of monetary policy on price and exchange rate stabilkity in Suriname. - JAHANGIR-ABDOELRAHMAN, Saira (1997)
Reviews the domestic credit policy of commercial banks in Suriname, and its influence on price and exchange rate objectives. Discusses the exchange rate policy as an instrument in stabilizing the Surinamese economy in 1995.